Extension Of Information Systems Success Model For The Gamification E-Learning System - Al-Muwassefi, Hala Najwan Sabeh (2022)
The existing literature depicts that graduates’ skills gap between industry expectations and academic preparation has become a trending phenomenon worldwide. Universities have been called to play a vital role to instil in these students the most sought skills in surviving this 21st Century. Hence, it signals the need to propose a new innovative system to enhance students’ skills and examine the net benefits of this system and the predictors of net benefits among university students. Accordingly, this research proposes the Login Career System, a gamification e-learning system, to improve students’ skills by integrating gamification features and certified e-learning courses. Besides, based on the integration of the updated DeLone & McLean Information Systems Success Model and the philosophy of expectancy theory, this study builds a theoretical model to govern the investigation of information quality, system quality, service quality, and collaboration quality as predictors of net benefits, use, and user satisfaction. Additionally, the model is built to investigate the use and user satisfaction as predictors of net benefits, whereas the use of the system is also examined as a predictor of user satisfaction. The research model was extended to include perceived future skills, perceived future personal characteristics, and perceived future labour market knowledge as the three outcome factors generated from the net benefits.